The Food of Athene noctua in nocturnal conditions as located in University of Agriculture, Faislabad - Zunaira Maqsood; Filza Ghafoor; Khazeema Naeem; Mujahid Niaz (Newinera Publisher, 2020)
This study was primarily focused on determining the availability of feeding niche of the little owl in University Campus. For this purpose, observations were made consecutively on the location of important sites in University Student’s Farm. This Farm is characterized by different types of tree species. Some of the important ones comprise Salmalia malabarica, Dalbergia sissoo, Cedrella toona, Terminalia arjuna and few others. The little owl mainly feeds on small insects and occasionally on very small mammals and perhaps on the small chicks. Small insects made the major portion of the diet of Athene noctua.